Hepatocellular Carcinoma: A Review (Journal of Renal and Hepatic Disorders, 2020)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Chronic liver disease due to viral hepatitis, alcohol, non-alcoholic fatty liver disease, etc are risk factors for HCC development. Triphasic contrast-enhanced computed tomography (CECT) and magnetic resonance imaging (MRI) abdomen are modalities for HCC diagnosis best for lesions >2 cm size. For lesions
Keywords: Barcelona clinic liver cance; checkpoint inhibitors; hepatocellular carcinoma; liver transplantation